Students’ motivational experiences across profiles of perceived need-supportive and need-thwarting teaching behaviors in physical education. - Burgueño Menjibar, Rafael; García-González, Luis; Abós, Ángel; Sevil-Serrano, Javier (Taylor & Francis, 2024)
Background: Consistent with self-determination theory (SDT), teachers may differ in the motivating style used to motivate students in physical education (PE). When relying on need-supportive behaviors, teachers attempt to provide students with opportunities for choices and initiative (autonomy support), valuable information and feedback (competence support), and an emotional and affective environment (relatedness support). Alternatively, teachers relying on need-thwarting behaviors tend to adopt a controlling language (autonomy thwarting), unclear goals toward the task (competence thwarting), and cold links with students (relatedness thwarting). While competence, autonomy, and relatedness supportive and thwarting behaviors are theoretically distinct in the instructional practice, every teaching behavior may cooccur to different degrees. Grounded in SDT, the only existing personcentered study in PE showed that PE teachers’ autonomy-supportive and controlling teaching behaviors can be combined through the students’ eyes, being associated with different motivational outcomes. Purpose: Adopting a person-centered approach, this research aimed to extend previous knowledge by examining how different combinations of students’ perceptions of autonomy, competence, and relatedness supportive and thwarting teaching behaviors are associated with students’ need satisfaction, need frustration, and motivation in PE. Method: A sample of 478 middle school students (53.97% girls) participated in the study. First, a two-step cluster analysis using autonomy, competence, and relatedness supportive and thwarting behaviors was run to identify different motivating teaching profiles. Subsequently, a multivariate analysis of covariance was conducted to examine differences between the retained clusters and students’ needbased experiences and motivational regulations.
https://openpolicyfinder.jisc.ac.uk/id/publication/5941?from=single_hit
Keywords: Educación física - Estudio y enseñanza; Profesores - Formación profesional; Investigación activa en educación; Motivating style; Need- supportive teaching; Controlling teaching; Teacher behavior; Self-determination theory